2022
DOI: 10.3390/fermentation8110621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Homo-Fermentative Lactic Acid Bacteria Inoculants on Fermentation Characteristics and Bacterial and Fungal Communities in Alfalfa Silage

Abstract: We evaluated the effects of a homo-fermentative lactic acid bacteria (homo-LAB) inoculant on the fermentation and microbial communities of alfalfa ensiled at two dry matter (DM) contents of 38 and 46% DM. At both DMs, alfalfa was treated or not with an inoculant containing Pediococcus acidilactici, Enterococcus faecium and Lactobacillus plantarum at a targeted application rate of 165,000 cfu/g of fresh weight and stored for 3, 30 and 60 days. Treatment with the inoculant resulted in a lower drop in pH and, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Vishniacozyma (also known as Cryptococcus ) has been isolated from soil and wheat, but there are limited reports regarding this genus in silage. It is reported that Vishniacozyma could assimilate lactic acid and D-lactose ( Tian et al, 2022 ; Li X. et al, 2022 ). Vishniacozyma was observed in both fresh and ensiled oat in the study, indicating the fresh oat might be subjected to soil contamination before ensiling.…”
Section: Discussionmentioning
confidence: 99%
“…Vishniacozyma (also known as Cryptococcus ) has been isolated from soil and wheat, but there are limited reports regarding this genus in silage. It is reported that Vishniacozyma could assimilate lactic acid and D-lactose ( Tian et al, 2022 ; Li X. et al, 2022 ). Vishniacozyma was observed in both fresh and ensiled oat in the study, indicating the fresh oat might be subjected to soil contamination before ensiling.…”
Section: Discussionmentioning
confidence: 99%
“…LAB strains have been increasingly used to preserve the silage quality and increase feed utilization rates in recent years [ 8 , 9 , 10 ]. Homofermentative and heterofermentative LAB inoculation has commonly been used to improve the fermentation quality of silage [ 11 , 12 , 13 ]. The product of homolactic fermentation is lactic acid, which promotes silage fermentation, rapidly lowers the pH of silage, and inhibits the growth of harmful microorganisms [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%